Bordetella Pertussis Adenylate Cyclase Toxin Does Not Possess a Phospholipase A Activity; Serine 606 and Aspartate 1079 Residues Are Not Involved in Target Cell Delivery of the Adenylyl Cyclase Enzyme Domain - Bumba, Ladislav; Masin, Jiri; Osickova, Adriana; Osicka, Radim; Sebo, Peter (Toxins, 2018)
The adenylate cyclase toxin-hemolysin (CyaA, ACT, or AC-Hly) plays a crucial role in virulence and airway colonization capacity of the whooping cough agent Bordetella pertussis. The toxin penetrates target cell membranes and exhibits three distinct biological activities. A population of CyaA conformers forms small cation-selective pores that permeabilize the cell membrane for potassium efflux, which can provoke colloid-osmotic (oncotic) cell lysis. The other two activities are due to CyaA conformers that transiently form calcium influx conduits in the target cell membrane and translocate the adenylate cyclase (AC) enzyme into cytosol of cells. A fourth putative biological activity has recently been reported; an intrinsic phospholipase A (PLA) activity was claimed to be associated with the CyaA polypeptide and be involved in the mechanism of translocation of the AC enzyme polypeptide across cell membrane lipid bilayer. However, the conclusions drawn by the authors contradicted their own results and we show them to be erroneous. We demonstrate that highly purified CyaA is devoid of any detectable phospholipase A1 activity and that contrary to the published claims, the two putative conserved phospholipase A catalytic residues, namely the Ser606 and Asp1079 residues, are not involved in the process of membrane translocation of the AC domain of CyaA across target membranes.
Keywords: Animals; buněčné linie; Aspartic Acid; adenylate cyclase toxin; erytrocyty; Phospholipases A; hemolýza; ovce; Adenylate Cyclase Toxin; Bordetella pertussis; serin; Mice; myši; Cell Line; AC domain translocation; kyselina asparagová; Erythrocytes; Sheep; fosfolipasy A; Hemolysis; Serine; zvířata; adenylátcyklasový toxin; phospholipase A activity